PENGARUH KOMBINASI ZAT PENGATUR TUMBUH INDOLE-3-BUTYRIC ACID (IBA) DAN 6-BENZIL AMINO PURIN (BAP) PADA KULTUR IN VITRO TUNAS AKSILAR ANGGUR (Vitis vinifera L.) VARIETAS PRABU BESTARI DAN JESTRO AG 86 - Cerianingsih, Made Wahyu; Astarini, Ida Ayu; Nurjaya, I Gusti Made Oka (Metamorfosa: Journal of Biological Sciences, 2015)
In vitro propagation study was carried out at Plant Tissue Culture Laboratory, Faculty of Agriculture, Udayana University. It was conducted using Completely Randomized Design with two factors.  The first factor was plant growth regulator (PGR), consist of nine concentration mixture of IBA (0, 0.5, 1 mg/L) and BAP (0, 1, 2 mg/L). The second factor was grape varieties, consisted of Prabu Bestari and Jestro Ag 86.  There were five replicates for each treatment combination. Variable observed included presence and absence of callus, percentage of callus growth, percentage of shoot growth, number of shoot per explants, emergence of shoots, percentage of root growth and number of roots per explants.  Data were statistically analyzed using Analysis of Variance (ANOVA).  When treatment showed a significant different (P < 0.05) or highly significant (P < 0.01) mean separation was conducted following Tukey Test. Data were analyzed using MINITAB Statistical Program. Results showed that PGR and varieties was highly significant for percent of callus growth.  PGR also showed significant effect on shoot growth percentage, while there was significant difference found on root growth percentage.  It can be concluded that combination of 1 mg/L IBA and 2 mg/L BAP was able to produce the highest percentage of callus growth. Addition of 2 mg/L BAP without IBA was able to produce the highest percentage of shoot growth. Percentage of root growth of Jestro Ag 86 was higher than Prabu Bestari.
Keywords: grape, in vitro propagation, IBA, BAP